2018
DOI: 10.1111/iju.13587
|View full text |Cite
|
Sign up to set email alerts
|

Tension‐free vaginal mesh surgery versus laparoscopic sacrocolpopexy for pelvic organ prolapse: Analysis of perioperative outcomes using a Japanese national inpatient database

Abstract: Both procedures offer favorable results for surgical treatment of pelvic organ prolapse. Overall, the tension-free vaginal mesh procedure seems to represent a good option for high-risk women, such as elderly patients, whereas laparoscopic sacrocolpopexy is useful for younger patients with a higher level of sexual activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 26 publications
(49 reference statements)
0
15
0
Order By: Relevance
“…After the introduction of TVM in 2005, both urologists and gynecologists became attracted to it because of its low invasiveness, uterine preservation and easy application to recurrent cases. [3][4][5][6] Although TVM decreased or was banned in Western countries after the 2011 FDA alert, 7,8 it remains as a core treatment option in East Asia due to fewer complications. [3][4][5][6]9,10 A questionnaire survey was carried out for surgeons who attended a national TVM meeting in 2010.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…After the introduction of TVM in 2005, both urologists and gynecologists became attracted to it because of its low invasiveness, uterine preservation and easy application to recurrent cases. [3][4][5][6] Although TVM decreased or was banned in Western countries after the 2011 FDA alert, 7,8 it remains as a core treatment option in East Asia due to fewer complications. [3][4][5][6]9,10 A questionnaire survey was carried out for surgeons who attended a national TVM meeting in 2010.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding POP, NTR, such as vaginal hysterectomy (with colporraphy) and colpocleisis, has been traditionally carried out by gynecologists, whereas anterior colporraphy has often been carried out by urologists. After the introduction of TVM in 2005, both urologists and gynecologists became attracted to it because of its low invasiveness, uterine preservation and easy application to recurrent cases 3–6 . Although TVM decreased or was banned in Western countries after the 2011 FDA alert, 7,8 it remains as a core treatment option in East Asia due to fewer complications 3–6,9,10 .…”
Section: Introductionmentioning
confidence: 99%
“…There were 20 eligible studies, including four RCTs [18][19][20][21][22] (there were two articles 20,21 about one RCT), four prospective studies [23][24][25][26] and 12 restrospective studies, [27][28][29][30][31][32][33][34][35][36][37][38] identified from the MEDLINE, EMBASE, Cochrane Library and clinicaltrials.gov databases. A PRISMA flow diagram depicting the study selection process is shown in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…Now, LSC including robot‐assisted LSC is becoming more popular due to its low invasiveness. After the 2011 FDA alert regarding mesh complications following TVM, a significantly greater number of surgeons have begun to use LSC 2 . Surgeons should be aware of LSC complications as they occur more often in the beginning of the learning curve.…”
Section: Discussionmentioning
confidence: 99%
“…Following the release, TVM decreased or was banned, then replaced by other prolapse surgeries including LSC in the United States and Europe. In Asian countries, although TVM remains as a leading surgical option due to relatively low complication rates, more doctors have introduced LSC, especially to younger or sexually active women 2 . As the number of LSC is increasing, problems related with LSC are beginning to be uncovered.…”
mentioning
confidence: 99%